How working-age population education and health of older people shape the burden of population aging: A comparative study of Macau, Hong Kong, and Singapore - Dong-mei Xue; Dong-mei Xue; Dong-mei Xue; Qian Bai; Qian Bai; Qian Bai; Ying Bian; Ying Bian; Ying Bian (Frontiers Media S.A., 2022)
Macau, Hong Kong and Singapore are all facing increasing population aging. Those aged 65 and over make up the old-age population. The working-age population refers to the population aged 15 to 64. Conventionally, the burden of population aging is measured by the Old-Age Dependency Ratio, which is the ratio of the old-age population to the working-age population. As life expectancy rises, depending exclusively on age to calculate the burden of aging hinders the development of effective anti-aging strategies. The working-age population's education and the elderly's health affect the aging burden's support and generator, respectively. Including them in the calculation gives us a fuller view of the burden of aging.ObjectiveTo compare the population aging burden in Macau, Hong Kong, and Singapore by including working-age population education and elderly health.MethodsThe overall, working-age and old-age population and proportion, as well as the Old-Age Dependency Ratio of Macau, Hong Kong, and Singapore, were collected from the World Bank database. The life expectancy at 65 was extracted from the 2022 World Population Prospect. The tertiary education rate of the working-age population and the self-rated health status of the old-age population were retrieved from governments' statistical reports. We then calculated the Education-Health Adjusted Old-Age Dependency Ratio, a set of four equations showing the support of the working-age population on the old-age population, where OADRh_t and OADRuh_t represent the burden of healthy and unhealthy old-age population on the working-age population with tertiary education; similarly, OADRh_nt and OADRuh_nt indicate the burden placed on the working-age population without tertiary education by healthy and unhealthy old-age population. Lastly, for comparison with the conventional Old-Age Dependency Ratio, we generated the Weighted Education-Health Adjusted Old-Age Dependency Ratio.ResultsHong Kong has the greatest old-age population proportion and Old-Age Dependency Ratio, yet its growth rates are moderate and stable, ranging from 0 to 4% and 0 to 6%, respectively. Macau and Singapore experienced sharper changes in old-age population proportion and the Old-Age Dependency Ratio, with Macau's Old-Age Dependency Ratio varying between −2.66 and 8.50% and Singapore's ranging from −1.53 to 9.70%. Three cities showed different patterns in four Education-Health Adjusted Old-Age Dependency Ratio indicators. In Macau, the OADRh_nt and OADRuh_nt increased by 0.4 and 6.2, while the OADRh_t and OADRuh_t decreased by 13.5 and 15.3 from 2004 to 2016. In Hong Kong, only the OADRuh_t fell by 9.4, and the other three increased from 2003 to 2015. In Singapore, the OADRh_nt and OADRh_t increased by 3.8 and 1.0, while OADRuh_nt and OADRuh_t decreased by 1.2 and 3.9 from 2007 to 2011. The Weighted Education-Health Adjusted Old-Age Dependency Ratios are all smaller than the conventional Old-Age Dependency Ratio in the three regions, particularly in Singapore. The Weighted Education-Health Adjusted Old-Age Dependency Ratio of Singapore was reduced by 9.5 to 30.5% compared with the conventional Old-Age Dependency Ratio, that of Hong Kong reduced by 6.2 to 22.5%, and that of Macau reduced by 4.4 to 16.1%.ConclusionThis is the first study to compare the aging burden in Macau, Hong Kong, and Singapore in connection to working-age population education and elderly health. With the new assessment, the burden of population aging in three regions has been reduced, showing that improving the education of the working-age population and maintaining older people's wellbeing can assist authorities to deal with population aging, especially in Macau and Hong Kong.